tanqībāt al-ma‘bad al-ṯānī ‘ašr (ma’bad al-‘ilāh Nabū) fī madīnah al-Ḥaḍr: al-mawsim al-rābi’ wa-l-‘ašrūn ’ām 1978 - ’Abdullāh, Muḥammad Ṣubḥī
Excavations at the Twelfth Temple (Nabû Temple) in the City of Hatra: 24th Season 1978; ersch. 1987